Nutraceutical and Food Preserving Importance of Laetiporus sulphureus - Sanem Bulam; Nebahat Şule Üstün; Aysun Pekşen (Turkish Journal of Agriculture: Food Science and Technology)
Laetiporus sulphureus (Bull.: Fr.) Murr. is popularly known as “sulphur polypore” or “chicken of the woods” due to its characteristic sulphur yellow coloured polypore’s and chicken-like taste and texture. This edible wild mushroom has been traditionally consumed as a source of nutrition and folk medicine in Asia and Europe for a long time. The numerous studies have shown that L. sulphureus nutritionally provides various key components such as carbohydrate, essential amino acids and fatty acids, vitamins, minerals, and fibre. Besides, the extracts prepared from fruiting bodies or mycelia of this mushroom have exhibited a number of medicinal properties such as immunomodulation, antitumor, anti-inflammatory, antioxidant, antimicrobial, and antihyperglysemic activities because of their biologically active components such as phenolics, triterpenes, and polysaccharides. L. sulphureus is also a suitable candidate to be used as a natural food preserving source.